Linking noncognitive factors back to second language learning: New theoretical directions. (November 2019) - Butler, Yuko Goto
Abstract: This special volume commentary addresses the significance of recent research on noncognitive factors for instructed second language acquisition, and considers this research in light of recent paradigm shifts in research on language learning as well as recent technological advances. Commonalities among the theories covered in this volume are assessed, and insights are offered into other issues that merit attention. The paper questions the value of distinguishing between cognitive and noncognitive individual differences, and looks at the nature of these theories within questions of domain specificity and the mechanism for interaction between internal states and external environments such as culture. The paper also considers alternative ways of measuring these factors to determine the true strength and direction of their influence in classroom learning, and discusses the role of deductive and inductive methods for scientific inquiries.